Respuestas

2013-03-01T04:09:11+01:00

entonces es:

               raiz(2+x) - raiz(2) 

lim       -------------------------

x->0                   x

 

 

bien:  multipliquemos por el conjugado del numerador:

 

               raiz(2+x) - raiz(2)  * raiz(2+x) + raiz(2)

lim       -------------------------

x->0                   x                 * raiz(2+x) + raiz(2)

 

               (2+x) - (2) 

lim       -------------------------

x->0     x*(raiz(2+x) + raiz(2))

 

 

                          x 

lim       -------------------------

x->0     x*(raiz(2+x) + raiz(2))

 

 

                                 1                               

lim       ------------------------------------

x->0             raiz(2+x) + raiz(2)      

 

ya se puede calcular sustituyendo x por 0

 

               1

------------------------

raiz(2+0) +raiz(2)

 

     1                    raiz(2)

-----------  =      ----------

 2raiz(2)                4